Patterns of Antibiotic Use in The One Hour Bundle Treatment of Sepsis - Syaputra, Adhika; Wijaya, Dadik Wahyu; Hanafie, Achsanuddin (CoinReads Media Prima, 2022)
Introduction: Sepsis and septic shock are major health problems, affecting millions of people worldwide and a leading cause of death. Administration of broad-spectrum empiric antibiotics as a one hour sepsis bundle treatment is associated with antimicrobial resistance which has various adverse effects and reduces the quality of health services. The aim of this research was to determine the pattern of empiric antibiotic use in the management of one hour bundle of sepsis at Haji Adam Malik General Hospital Medan. Method: This study used a descriptive method from November 2022 to December 2022 in the Emergency Room (ER), Medical Inpatient Room, Surgical Inpatient Room, and Adult Intensive Care Unit (ICU) of Haji Adam Malik General Hospital Medan. This study used a consecutive sampling technique to recruit 42 sepsis patients who were given a one hour bundle of sepsis according to the inclusion and exclusion criteria. This descriptive analysis was used to determine the characteristics of the sample, namely age, sex, culture results, and antibiotic sensitivity test results. Results: The most common use of antibiotics in the one hour bundle sepsis strategy was ceftriaxone 1 gram in 20 patients (47.6%), Ampicillin-Sulbactam 1.5 grams in 10 patients (23.8%), Levofloxacin 750 mg in 6 patients (14.3%), Meropenem 1 gram in 4 patients (9.5%), and Ciprofloxacin 200 mg in 2 patients (4.8%). Conclusion: Antibiotic administration time is less than 1 hour in the one hour bundle strategy carried out in the ER. Most of the antibiotics given are in accordance with the antibiotic sensitivity test results, but there are still some patients who still experience resistance to the antibiotics.given so it is important to always or immediately carry out culture and sensitivity tests on patients so that the antibiotics given can be more optimal